2020
DOI: 10.3897/ap.2.e1353
|View full text |Cite
|
Sign up to set email alerts
|

Social and Educational Barriers to Inclusive Education of Individuals with Special Health Needs

Abstract: Inclusive education development has objectified new tasks for teachers on the individualization of training and upbringing learners with special health needs. At the same time, significant efforts have been made by the pedagogical community to solve these tasks causing challenges for teachers, increasing the risks of inclusive education and reducing the quality of students' achievements. Studying the barriers in teachers' perceptions of the inclusive education and its principles, on the one hand, and teachers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
4
4
0
Order By: Relevance
“…This finding is in line with these studies (Alhammad, 2017;Alkhateeb et al, 2016;Ambia, & Rahman, 2021;DEEWR, 2012;Kuzmicheva & Afonkina, 2020;Hadidi & Alkhateeb, 2015;Muthukrishna et al, 2016;Sharma et al, 2019) which found that teachers, parents, and students had negative, stereotypical and biased attitudes towards students with SEN. Nevertheless, the finding of negative attitudes of teachers, parents, and students towards including students with SEND is inconsistent with a study by Hussein (2019) which found that attitudes of teachers, parents, and students were positive and improving.…”
Section: Negative Attitudes Of Teaching Staff Parents and Studentssupporting
confidence: 86%
See 3 more Smart Citations
“…This finding is in line with these studies (Alhammad, 2017;Alkhateeb et al, 2016;Ambia, & Rahman, 2021;DEEWR, 2012;Kuzmicheva & Afonkina, 2020;Hadidi & Alkhateeb, 2015;Muthukrishna et al, 2016;Sharma et al, 2019) which found that teachers, parents, and students had negative, stereotypical and biased attitudes towards students with SEN. Nevertheless, the finding of negative attitudes of teachers, parents, and students towards including students with SEND is inconsistent with a study by Hussein (2019) which found that attitudes of teachers, parents, and students were positive and improving.…”
Section: Negative Attitudes Of Teaching Staff Parents and Studentssupporting
confidence: 86%
“…1. Pressures on Funding (Ambia, & Rahman, 2021;Department of Education, Employment and Workplace Relations [DEEWR], 2012; Kuzmicheva & Afonkina, 2020;Sharma, Armstrong, Merumeru, Simi, & Yared, 2019;Muthukrishna et al, 2016) Wapling ( 2016) contends that education systems in low and middle-income countries (LMICs) may be providing little to no support at all for its implementation at the level of direction, resources, and skills. United Nations Children's Fund [UNICEF] and World Health Organization [WHO] (2015) emphasize that ATs are a necessity for children with disabilities to enjoy their life and rights.…”
Section: Barriers To Iementioning
confidence: 99%
See 2 more Smart Citations
“…However, this problem has not yet been solved. Nevertheless, the evolution of the pedagogical consciousness and, accordingly, the professional activity of the teacher is moving in the direction of studying the characteristics and opportunities of the child, taking into account the diversity of educational needs of students in inclusive education and the obvious understanding of such changes in order to achieve high educational results (Kuzmicheva & Afonkina, 2020).…”
Section: Introductionmentioning
confidence: 99%